Patents for biotechnology inventions in TRIPs - Rao, C. Niranjan (2002)
While the Trade-Related Aspects of Intellectual Property Rights Agreement of the Uruguay Round has been controversial, Article 27 (3) (b) of this agreement is more so. It pertains to patenting of biotechnology inventions. The origin of this article may be traced to conventions in European countries, and also discuss the biotechnology patenting question under the 1970 Patent Act in India. - Reproduced.
Keywords: Intellectual property; Biotechnology; Patents